Discipline and development : middle classes and prosperity in East Asia and Latin America - Davis, Diane E., 1953- (Cambridge University Press, 2004)
Perhaps the most commonly held assumption in the field of development is that middle classes are the bounty of economic modernization and growth. As countries gradually transcend their agrarian past and become urbanized and industrialized, so the logic goes, middle classes emerge and gain in number, complexity, cultural influence, social prominence, and political authority. Yet this is only half the story. Middle classes shape industrial and economic development, they are not merely its product; the particular ways in which middle classes shape themselves - and the ways historical conditions shape them - influence development trajectories in multiple ways. This is the story of South Korea's and Taiwan's economic successes and Argentina's and Mexico's relative 'failures' through an examination of their rural middle classes and disciplinary capacities.